Evaluasi Akurasi Purwarupa Kalibrator Fetal Doppler untuk Kesejahteraan Ibu dan Anak: Studi Observasional di Puskesmas Kartasura - Marissa Usie Shania Devi (Masker Medika, 2024)
Introduction: Fetal Doppler is used to monitor fetal heart rate (FHR) and prevent delayed diagnosis of critical conditions such as congenital heart disease (CHD). The inaccuracy of an uncalibrated device can have serious consequences. This study evaluated the accuracy of a prototype Fetal Doppler calibrator in measuring DJJ on several types of devices: calibrated, new, and uncalibrated. Methods: This observational study with an analytic approach was conducted at the Kartasura Health Center in March-June 2024. Six Fetal Doppler devices were tested, including one calibrated device, two new devices, and three uncalibrated devices. Measurement results were expressed in beats per minute (BPM) and analyzed using an independent t-test to test for differences between devices. Results: No significant differences were found between the prototype calibrator and the various devices tested (p > 0.05). However, the uncalibrated devices showed a higher level of result variability than the new and calibrated devices. Discussion: Higher variability in uncalibrated devices indicates the importance of periodic calibration to ensure consistency of DJJ measurements. These results are consistent with previous studies emphasizing that uncalibrated medical devices have the potential to decrease accuracy. The calibrator tested was able to provide accurate results, supporting its use in effectively monitoring fetal health. Conclusion: The prototype Fetal Doppler calibrator was able to provide accurate results on a variety of device types. The importance of routine calibration is emphasized to maintain monitoring quality and support early detection of CHD, which is crucial in improving the quality of maternal and child health services.